Prevalence and distribution of respiratory pathogens in pediatric acute respiratory infections in Putian, China - Jinwei Zhu; Suqing Wu; Yan Chen; Liping Zheng (BMC Infectious Diseases)
Abstract Background Acute Respiratory Infections (ARIs) are a significant source of morbidity among pediatric populations. This study aimed to investigate the prevalence and distribution of respiratory pathogens in pediatric ARIs in Putian, China. Methods This retrospective study included 3,790 pediatric patients with suspected ARIs, evaluated between March 2023 and February 2024. Nasopharyngeal swabs were obtained and analyzed via reverse-transcription polymerase chain reaction (RT-PCR) to detect eleven common respiratory pathogens. Statistical analyses were conducted to evaluate the distribution of these pathogens across various patient demographics, including gender, age, and season. Results This study included 3,790 pediatric patients under 14 years (median age: 4.3 years, IQR: 1–7). Pathogen positivity was 78.9%, with higher rates in school-age children and during autumn and winter (P < 0.001), with Mycoplasma pneumoniae (Mp) as the most common pathogen (33.4%), followed by human rhinovirus (HRV; 15.0%) and human respiratory syncytial virus (HRSV; 12.1%). Single-pathogen detections dominated (81.9%), while co-detections (18.1%) were primarily dual-pathogen cases, with HRV + Mp as the leading combination. Pathogen distribution varied significantly by age: Mp detection rates escalated with age, peaking in school-age children, while HRSV and HRV predominated in infants and toddlers. Seasonal trends revealed distinct pathogen activity: Influenza A (InfA) peaked during spring, Mp during autumn and winter, and HRSV during summer (P < 0.001). Logistic regression analysis identified significant associations: InfA, human adenovirus (HADV), and Influenza B (InfB) were linked with acute upper respiratory infections (AURIs), while Mp, human metapneumovirus (HMPV), human parainfluenza virus (HPIV), and HRSV correlated with acute lower respiratory infections (ALRIs) (P < 0.05). Conclusion This study provides comprehensive insights into the prevalence and temporal patterns of respiratory pathogens among hospitalized children with ARIs in Putian, China. Mp, HRV, and HRSV were the predominant pathogens, with significant variations by age and season. Limitations include the one-year duration and the focus on hospitalized patients. Future studies should extend surveillance to outpatient and emergency settings to obtain a broader understanding of ARI epidemiology.